Clarifying the two facets of Self-Oriented Perfectionism: influences on affect and the Big Five traits of personality in children - Vicent, María; Inglés, Cándido J.; Sanmartín, Ricardo; Gonzálvez, Carolina; Aparicio-Flores, María del Pilar; García-Fernández, José Manuel (Anales de Psicología / Annals of Psychology, 2019)
This study analyses the relationship between the perfectionism dimensions, i.e. Self-Oriented Perfectionism-Critical (SOP-C) and Self-Oriented Perfectionism-Striving (SOP-S), and affect and the Big Five traits of personality in a sample of 804 Spanish students aged 8 to 11 (M = 9.57; DE = 1.12). Student’s t test, Cohen’s d index and logistic regression analysis were used. The high SOP-C group scored significantly higher than their peers having low SOP-C on Negative Affect and Neuroticism, and lower on Positive Affect, Agreeableness, Consciousness and Openness to Experience. To the contrary, students with high SOP-S scored significantly higher on all adaptive dimensions (i.e. Positive Affect, Extraversion, Agreeableness, Consciousness and Openness to Experience), and lower on Negative Affect and Neuroticism. Effect sizes were small for most of statistically significant differences. These findings were also supported by regression analysis. Results are discussed in light of the debate on the adaptive or maladaptive nature of Self-Oriented Perfectionism.